The Influence of Diversification and Corporate Governance Implementation on Company Value with Company Size as a Moderation Model in Manufacturing Companies Listed on the Stock Exchange from 2020 to 2022 - Natalia Kristanti, Yosephine; Mulya, Hadri (Journal of World Science, 2024)
This study aims to analyze the influence of diversification and corporate governance implementation on firm value, with firm size as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange during the period 2020-2022. The research method employed is causal research. The population of the study comprises 193 manufacturing companies listed on the Indonesia Stock Exchange, with classical assumption tests and hypothesis testing used as analytical techniques. The results of the analysis indicate that diversification does not have a significant influence on firm value. However, the independence of the board of commissioners and the competence of the audit committee significantly affect firm value. Additionally, firm size serves as a significant moderating variable in influencing the relationship between the independence of the board of commissioners, competence of the audit committee, and firm value. The implications of these findings are to provide valuable insights for practitioners and academics in understanding the factors influencing firm value in the Indonesian capital market. This underscores the importance of effective corporate governance implementation, particularly through enhancing the independence of the board of commissioners and the competence of the audit committee, as well as a better understanding of how firm size can moderate the relationship between these factors and firm value.